1978
DOI: 10.1159/000241062
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia Connected with Parenteral Administration of Higher Amounts of Fluids in Premature Infants

Abstract: During a study on the influence of different amounts of fluid intake on water and electrolyte metabolism in the first 3 days of life, a high incidence of hyperbilirubinemia was observed in infants receiving a large water load (150 ml/kg/24 h) intravenously. The amount of meconium excreted during the 3-day period in newborns with total parenteral alimentation was significantly lower than in controls. Hyperbilirubinemia is considered to be due to the enterohepatic circulation of bilirubin present in the retained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…5 This was supported by clinical observations that earlier meconium evacuation was indeed associated with lower bilirubin levels and decreased risk for clinically significant neonatal jaundice. [10][11][12][13][14][15] Several studies have evaluated the effect of stimulating early meconium evacuation on serum bilirubin levels. Cotrell et al 9 have shown that rectal stimulation not only enhanced early meconium evacuation, but also caused a mean reduction of 1 mg/dL in serum bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This was supported by clinical observations that earlier meconium evacuation was indeed associated with lower bilirubin levels and decreased risk for clinically significant neonatal jaundice. [10][11][12][13][14][15] Several studies have evaluated the effect of stimulating early meconium evacuation on serum bilirubin levels. Cotrell et al 9 have shown that rectal stimulation not only enhanced early meconium evacuation, but also caused a mean reduction of 1 mg/dL in serum bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous studies have shown that early meconium evacuation was associated with lower bilirubin levels and decreased risk for clinically significant neonatal jaundice. [10][11][12][13][14][15] It thus seemed plausible that meconium evacuation facilitated with the use of glycerin suppositories might prevent the effect of increased enterohepatic recirculation on serum bilirubin, thus decreasing the risk of neonatal jaundice. However, to date, the data are inconclusive; some claim that it works, 16 whereas others show no effect.…”
mentioning
confidence: 99%